2023
DOI: 10.1002/anie.202300694
|View full text |Cite
|
Sign up to set email alerts
|

Dendronized DNA Chimeras Harness Scavenger Receptors To Degrade Cell Membrane Proteins

Abstract: Bispecific chimeras bridging cell membrane proteins with lysosome‐trafficking receptors (LTRs) provide an effective therapeutic approach through lysosomal degradation of disease‐relevant targets. Here, we report a novel dendronized DNA chimera (DENTAC) strategy that uses a dendritic DNA to engage cell surface scavenger receptors (SRs) as LTR. Using bioorthogonal strain‐promoted alkyne‐azide cycloaddition to conjugate the dendritic DNA with protein binder, the resulting DENTAC is able to traffic the protein tar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 55 publications
(28 reference statements)
1
30
0
Order By: Relevance
“…The red fluorescence was visualized after the incubation of tumor cells with RhB@MI 7 -β-CD/SA NPs for 2 h and co-localized with the green fluorescence of endosomes/lysosomes (shown as yellow fluorescence). The reasons may be attributed to the fact that SR on the surface of tumor cells acts as an anion ligand-binding receptor, while the polyanionic nanomaterials can target SR and then induce drug internalization into lysosomes via caveolae-mediated endocytosis . The results demonstrated that RhB@MI 7 -β-CD/SA NPs were initially internalized by tumor cells, then transported to endosomes/lysosomes for intracellular trafficking, ultimately leading to the cargo release and effective accumulation inside tumor cells. , …”
Section: Resultsmentioning
confidence: 99%
“…The red fluorescence was visualized after the incubation of tumor cells with RhB@MI 7 -β-CD/SA NPs for 2 h and co-localized with the green fluorescence of endosomes/lysosomes (shown as yellow fluorescence). The reasons may be attributed to the fact that SR on the surface of tumor cells acts as an anion ligand-binding receptor, while the polyanionic nanomaterials can target SR and then induce drug internalization into lysosomes via caveolae-mediated endocytosis . The results demonstrated that RhB@MI 7 -β-CD/SA NPs were initially internalized by tumor cells, then transported to endosomes/lysosomes for intracellular trafficking, ultimately leading to the cargo release and effective accumulation inside tumor cells. , …”
Section: Resultsmentioning
confidence: 99%
“…The rate capability result demonstrates that the N,S-C@Bi/CNT anode has superior rating performance in high current density when compared with previously reported Bi anode materials. 37,43–48 In addition, the galvanostatic charge–discharge platform profiles of these two samples at different current densities were tested, as shown in Fig. S7 †.…”
Section: Resultsmentioning
confidence: 99%
“…In this context, Zhu et al have reported a Diels–Alder reaction of 2-trifluoroacetamido-1,3-dienes and α,β-unsaturated carbonyl compounds to afford 1-trifluoroacetamido cyclohex-1-ene derivatives 27 (Scheme 26). 96 The exploration of diverse dienophiles in the CPA-catalyzed cycloaddition reaction produced moderate to excellent yields with good to excellent enantioselectivities (52–96% yields, 83–99% ee). Then, 4-aryl or 4-alkyl substituted dienes were evaluated.…”
Section: Addition Reactionsmentioning
confidence: 99%